The Influence of Organizational Culture on Employee Performance With Work Motivation as an Intervening Variable at Bpjs Employment Padang Sidimpuan Branch Office and Pematang Siantar Branch Office - MARYANTO PURBA; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
Bad human resources will cause an organization to have big or small problems, this will definitely happen if human resources in the organization are low. Human Resources (HR) in general are productive individuals who work as drivers of an organization, both within institutions and companies who function as assets and must be trained and developed. The phenomenon that occurs at BPJS Ketenagakerjaan, Padang Sidimpuan and Pematangsiantar branch offices, each branch has its own problems, but there are similarities between the mistakes of both organizations, namely a poor and toxic organizational culture that reduces employee performance, this culture makes employees less enthusiastic about working. Due to the lack of positive interaction between employees with each other, a culture of indifference also mushrooms in that place. Poor work causes employee performance to decline. This is due to a lack of work motivation and strict arrangements to change a toxic organizational culture into a positive organizational culture. in every job and communication. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with a value of 0.398 and a significant value of 0.000. Organizational culture has a positive and significant effect on work motivation with a value of 0.896 and a significant value of 0.000. Work Motivation has a positive and significant effect on Employee Performance with a value of 0.542 and a significant value of 0.000. Organizational culture has a positive and significant effect on employee performance indirectly through work motivation with a value of 0.485 and a significant value of 0.000.